The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1002/mrm.1910340219
|View full text |Cite
|
Sign up to set email alerts
|

A computer simulation of the static magnetic field distribution in the human head

Abstract: Distortion of the static magnetic field inside the human head is dependent on regional tissue susceptibility variations and geometrical shape. These effects result in resonance line broadening and frequency shifts and consequently, intensity and spatial errors in both magnetic resonance imaging (MRI) and magnetic resonance (MR) spectroscopy. To calculate the field distortion due to the susceptibility's geometry, two dimensional (2D) finite element analysis was applied to simulate the field distribution in a 2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 30 publications
7
37
0
Order By: Relevance
“…The calculated result was in good agreement with the field map obtained by using the DANTE tagging image sequence (25). The field distribution in localized regions was evaluated by using the magnetic field histogram technique, which provides the frequency shift and line broadening of NMR signals at specific regions of interest.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…The calculated result was in good agreement with the field map obtained by using the DANTE tagging image sequence (25). The field distribution in localized regions was evaluated by using the magnetic field histogram technique, which provides the frequency shift and line broadening of NMR signals at specific regions of interest.…”
Section: Introductionsupporting
confidence: 76%
“…We have previously applied the finite element analysis method to calculate the static magnetic field distribution for a two-dimensional (2D) human head model in the sagittal plane (25). The calculated result was in good agreement with the field map obtained by using the DANTE tagging image sequence (25).…”
Section: Introductionsupporting
confidence: 53%
“…For this study, the magnetic field homogeneity was optimal in the superior prefrontal cortex. A two-dimensional calculation of magnetic field mapping of the human head (20) showed that coronal planes at this location of the brain suffer from large magnetic field deviations in the inferior regions (because of air-filled cavities and sinuses), whereas the magnetic field is very homogeneous in the superior parts. Magnetic field mapping with optimal shimming of the human brain at 2.1 T has confirmed these theoretical findings (21).…”
Section: Resultsmentioning
confidence: 98%
“…For B 0 mapping, typically a single, relatively short phase evolution time is used because of the complexities associated with unwrapping in two or three dimensions (10 -12). In the temporal lobe, strong susceptibility effects arising from the air-filled sinuses and ear canals result in strong high-order gradients (1-2 ppm/cm) (13,14). Coupled with the anatomical variability, this often results in initial frequency distributions with ranges of several hundred hertz.…”
mentioning
confidence: 99%